(3efXheI aj CQHYjf MOjKkGs - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s
(3ChdgG (B:s
(3HSe GdEdg GdhGMO GdefGf GdhGMO GdQMje Pi GdEMSGf fMeOg MeOkG jajO MaXkG ef GdQLje ci fLjO MaXkG s
(3BNQgG (B:s
(3eWgQkG ef QLS TQc fLS eYeQkG HCfaS hCbOS eOi GdOghQ eG HOG UHGM heG ESJfGQ ai GdOLG eUHGM JeJ hHGdNjQGJ Gddg YeJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs